Sequential Camouflage of the arachno-6,9-C2B8H14 Cage by Substituents - Bakardjiev, Mario; Štíbr, Bohumil; Holub, Josef; Tok, Oleg L; Švec, Petr; Růžičková, Zdeňka; Růžička, Aleš (Inorganic chemistry, 2016)
Sequential methylation of arachno-6,9-C2B8H14 (1) led to a series of methyl derivatives and finally to the camouflaging of all boron positions by mixed persubstitution. Thus, deprotonation of 1 produced the [arachno-6,9-C2B8H13] anion (1(-)), the methylation of which with MeI in tetrahydrofuran proceeded on the open-face boron vertexes with the formation of 5-Me-arachno-6,9-C2B8H13 (2; yield 28%) and 5,8-Me2-arachno-6,9-C2B8H12 (3; yield 36%). Observed in this reaction was also a side formation of 2-Me-closo-1,6-C2B8H9 (4; yield 6%).The electrophilic AlCl3-catalyzed CH3(+) attack of the neutral 1 in neat MeI at ambient temperature afforded 1,3-Me2-arachno-6,9-C2B8H12 (5), while a 76-h heating at 120 °C generated a mixture of the di- and triiodo derivatives 1,2,3,4,8,10-Me6-5,7-I2-arachno-6,9-C2B8H6 (6) and 1,2,3,4,7-Me5-5,7,10-I3-arachno-6,9-C2B8H6 (7). On the other hand, a HOTf-catalyzed reaction between 1 and MeOTf at reflux resulted in the isolation of 2-TfO-1,3.4,5,7,8,10-Me7-arachno-6,9-C2B8H6 (8; Tf = CF3SO2; yield 65%). The compounds were characterized by multinuclear ((11)B, (1)H, (13)C, and (19)F) NMR spectroscopy, mass spectrometry, and elemental analysis, and the structures of compounds 1, 1(-), 5, and 6 were established by X-ray diffraction analysis.